Graphene oxide layers modified by light energetic ions. Issue 16 (5th April 2017) - Malinský, Petr; Macková, Anna; Mikšová, Romana; Kováčiková, Helena; Cutroneo, Mariapompea; Luxa, Jan; Bouša, Daniel; Štrochová, Beata; Sofer, Zdeněk
Abstract : In this paper, the effect of light ion irradiation on graphene oxide foil structure and composition was studied. Abstract : In this paper, the effect of light ion irradiation on graphene oxide foil structure and composition was studied. Due to the excellent properties of graphene based materials suitable for application in electronics, optoelectronics, micro-mechanics and space technologies, the interaction of energetic ions with graphene based structures is worth studying. From the fundamental point of view, it is also interesting to get information about graphene oxide structure modification and the possible functional properties after irradiation by energetic ions. The light ion irradiation of graphene oxide (GO) foil was performed using 2.5 MeV H + and 5.1 MeV He 2+ ions. The change in the elemental composition of the GO foils after ion irradiation was investigated using Rutherford Backscattering Spectrometry and Elastic Recoil Detection Analysis. The influence of ion irradiation was further studied by microscopy methods. The chemical composition and structural changes of the GO foil surface were characterized by spectroscopy techniques including XPS, FTIR and Raman spectroscopy. Although the results of ion beam analysis indicated no significant compositional changes in the bulk of GO foils connected to ion irradiation, XPS, ATR-FTIR and Raman spectroscopy revealed reduction and removal of oxygen functionalities on the surface of graphene oxide. This reduction leads to a surface resistivity decrease after ion irradiation dependent on the ion species, fluence and energy.